The Effect of Purple Sweet Potato Flour (Ipomoea batatas L) as Wheat Flour Substitution on Physicochemical and Sensory Properties of Crackers: sweet potato crackers - Kurniati, Mila; Muhaimin, Muhaimin; Ulyarti, Ulyarti (Jurnal Bio-Geo Material Dan Energi, 2024)
The changes in main ingredients may affect the characteristics of cracker. This study aimed to determine the effect of purple sweet potato flour as a substitute for wheat flour on the physicochemical and sensory properties of crackers. This study used a Completely Randomized Design (CRD) consisting of 6 levels of purple sweet potato flour concentration as treatment (0%, 10%, 20%, 30%, 40%, and 50%) and 3 replications. The concentration of purple sweet potato flour has shown a significant effect on volume development, brightness value (L*), anthocyanin content, and sensory properties (color, taste and overall acceptance), but has not shown significant effect on the texture and sensory property (texture) of crackers. The substitution of 50% wheat using purple sweet potato flour produced the best crackers with hardness 1098.80 gF, development volume 19,33%, L* 72, a* 30, b* 4.33 and the anthocyanin contents of 162.02 mg of Cyanidin 3-glucoside/100g. The cracker contains 6.25% moisture content, 3.00% ash, 7.47% protein, 19.00% fat, 1.00% crude fiber and 64.28% carbohydrate.